2021
DOI: 10.1177/10600280211013581
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and Impact of Intravenous Medication Fluid Administration in Critically Ill Patients With Acute Respiratory Failure

Abstract: Background: Positive fluid balance early in critical illness is associated with poor outcomes. Reducing intravenous medication volume may mitigate volume overload. Objective: Assessment of fluid and medication administration and clinical outcomes in acute respiratory failure. Methods: Single-center, prospective observational study of hemodynamically stable adult patients in a medical intensive care unit (MICU) with acute respiratory failure. Results: Median cumulative total intake volume was 12 890 (interquart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…The authors estimated a 38% reduction in cumulative IV medication diluent volume with the implementation of SVI and found cumulative fluid volume was associated with ventilator-free days and medical ICU length of stay. 16 The present study found a reduction of 29.9% and 29.6% in cumulative vasopressor and antimicrobial diluent volumes, respectively. These findings align with those estimated in the aforementioned study; however, not all vasopressor and antimicrobial medication diluent volumes were able to be optimized with the current study protocol due to operational and logistical limitations (Supplemental Table 1).…”
Section: Discussionsupporting
confidence: 53%
See 4 more Smart Citations
“…The authors estimated a 38% reduction in cumulative IV medication diluent volume with the implementation of SVI and found cumulative fluid volume was associated with ventilator-free days and medical ICU length of stay. 16 The present study found a reduction of 29.9% and 29.6% in cumulative vasopressor and antimicrobial diluent volumes, respectively. These findings align with those estimated in the aforementioned study; however, not all vasopressor and antimicrobial medication diluent volumes were able to be optimized with the current study protocol due to operational and logistical limitations (Supplemental Table 1).…”
Section: Discussionsupporting
confidence: 53%
“…27 One prior study by Gonzales et al investigated the impact of medication diluent volume optimization and was a noninterventional study of IV medication fluid administration in critically ill patients with acute respiratory failure. 16 This study found antimicrobial, electrolyte, sedative, and analgesic medications contributed the most to medication diluent volume. The authors estimated a 38% reduction in cumulative IV medication diluent volume with the implementation of SVI and found cumulative fluid volume was associated with ventilator-free days and medical ICU length of stay.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations